CURRICULUM DESIGN OF ENGLISH FOR INFORMATION TECHNOLOGY AT STIKOM DINAMIKA BANGSA JAMBI: A CASE STUDY OF ENGLISH FOR SPECIFIC PURPOSE - Maitri Rahmadhani (Jurnal Sintaksis, 2020)
This research is considered as a Qualitative Research. The objectives of this research are (1 To find out the appropriate English materials for the IT students at STIKOM Dinamika Bangsa Jambi and (2) To construct the English curriculum design for the IT students at STIKOM Dinamika Bangsa Jambi. The data are analysed based on Bogdan and Biklen’s stages/steps; searching the data, arranging the data and interpreting. The validity of the data is taken by applying investigator triangulation i.e. by assessing the analysis to two key informants; native speakers of English. Based on the analysis, it is found that: (1) the need of English speaking skill is taken as the first concern, (2) both the 8th semester students and the Alumni of STIKOM Dinamika Bangsa Jambi have lack on business English i.e. the English used for working, (3) there should be improvement of teaching method in English classroom, and the materials taught in English class should be concern about speaking and reading, (4) several aspects, such as motivation, might also affect the English mastery, (5) the previous course syllabus be one of gudances to contstruct a better curriculum design, (6) Speaking and Reading must be the priority and writing as the additional one to be taught at STIKOM Dinamika Bangsa Jambi to help the students to face the working atmosphere.